Phylogenetic Analysis of West Nile Virus, Nuevo Leon State, Mexico - Blitvich, Bradley J.; Fernández Salas, Ildefonso; Contreras Cordero, Juan Francisco; Loroño Pino, María Alba; Marlenee, Nicole L.; Díaz, Francisco J.; González Rojas, José Ignacio; Obregón Martínez, Nelson; Chiu García, Jorge A.; Black, William C.; Beaty, Barry J. (2004)
West Nile virus RNA was detected in brain tissue from a horse that died in June 2003 in Nuevo Leon State, Mexico. Nucleotide sequencing and phylogenetic analysis of the premembrane and envelope genes showed that the virus was most closely related to West Nile virus isolates collected in Texas in 2002.